GIS: an introduction to mapping technologies - McHaffie, Patrick; Hwang, Sungsoon; Follett, Cassie (London CRC Press, 2023)
The second edition of this introductory GIS textbook is thoroughly rewritten and updated to respond to the demand for critical engagement with technologies that address relevant issues across several disciplines preparing students for higher-level work in geotechnologies. Chapters are arranged to (1) build competence in fundamental skills, (2) explore applications of higher-level managerial and analytical functions that are typically called upon in public, nonprofit, and private sector milieu, and (3) propose and detail a template for organizing, executing, and completing a GIS project successfully. This interests all users from beginners to experienced professionals.
Keywords: Geodesy; Geographic information systems; Information storage and retrieval systems -- Geography